2021
DOI: 10.1038/s41598-021-02211-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of APOB polymorphism rs562338 (G/A) on serum proteome of coronary artery disease patients: a “proteogenomic” approach

Abstract: In the current study, APOB (rs1052031) genotype-guided proteomic analysis was performed in a cohort of Pakistani population. A total of 700 study subjects, including Coronary Artery Disease (CAD) patients (n = 480) and healthy individuals (n = 220) as a control group were included in the study. Genotyping was carried out by using tetra primer-amplification refractory mutation system-based polymerase chain reaction (T-ARMS-PCR) whereas mass spectrometry (Orbitrap MS) was used for label free quantification of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
1
5
0
Order By: Relevance
“…18,19 According to a study done by Zafar et al on rs562338 (G/A) ApoB gene polymorphism, individuals with AA genotypes experience altered serum lipid profiles more frequently than those with GG genotypes. 11 Similar findings were found in the Maonan and Han populations, except that they focused on the rs1042034 (G/A) ApoB gene polymorphism. They found that various rs1042034 (G/A) genotypes were linked to dyslipidemia.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…18,19 According to a study done by Zafar et al on rs562338 (G/A) ApoB gene polymorphism, individuals with AA genotypes experience altered serum lipid profiles more frequently than those with GG genotypes. 11 Similar findings were found in the Maonan and Han populations, except that they focused on the rs1042034 (G/A) ApoB gene polymorphism. They found that various rs1042034 (G/A) genotypes were linked to dyslipidemia.…”
Section: Discussionsupporting
confidence: 67%
“…The three alleles that were produced were GG (381 bp), AA (354 bp) and GA; both bands were present in addition to the 672 bp control band. The PCR amplification conditions were 95°C for 5 min, 35 cycles of amplification at 95°C for 1 min, 64.3°C for 1 min, 72°C for 30 s and final elongation at 72°C for 10 min 11 Genotype analysis of rs17240441 SNP To analyze the signal peptide of the gene 5 ApoB for insertion/deletion (I/D) polymorphisms, the oligonucleotide sequences 5CAG CTG GCG ATG GAC CCG CCGA3 as the five primers and 5CCA ATG ACA AAA TCC GTG AGG 3 as the three primers were used to create a primer combination that was intended to generate the first exon on the ApoB gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the samples were centrifuged (Centrifuge 5417R, Eppendorf, Germany) at 16000 rpm, 4°C for 20 min and protein concentrations were measured using Qubit™ Protein Assay kit (Invitrogen, Thermo Fisher Scientific, USA). The tryptic digestion of proteins and desalting of peptides was performed, using a previously reported method 26,27 . The peptide concentrations of samples were then quantified by the Qubit™ Protein Assay kit and dried peptides were kept at −20°C until further processing.…”
Section: Methodsmentioning
confidence: 99%
“…The tryptic digestion of proteins and desalting of peptides was performed, using a previously reported method. 26,27 The peptide concentrations of samples were then quantified by the Qubit™ Protein Assay kit and dried peptides were kept at À20 C until further processing.…”
Section: Sample Preparationmentioning
confidence: 99%